MEMBANGUN KETANGGUHAN KOMUNITAS MELALUI DASAWISMA SIAGA BENCANA DI DESA BUNGURASIH KECAMATAN WARU KABUPATEN SIDOARJO - Hendro Wardhono; Priyanto Priyanto; Nur Sayidah; Siti Marwiyah (Universitas Islam Darul Ulum Lamongan, 2022)
Women as part of society are often 'made' more vulnerable to disasters, through the social roles they develop. Women have less access to resources, for example: social networks and influence, transportation, information, skills (including literacy), control of natural and economic resources, individual mobility, security of housing and work, guarantees of freedom from violence, and ownership of control over decision making. In fact, they are all important in disaster management programs or activities. In essence, women and men respond differently to crisis or disaster situations. In an effort to fight violence, survive and help those who are their dependents, women and men will take different actions. This may be obvious, but experience to date has shown that the gender aspect of a crisis or disaster is often overlooked and not visible when planning interventions. Furthermore, Dasa Wisma is very useful for empowering and increasing the capacity of its members in dealing with disasters in their homes. The Dasa Wisma group and its network have spread to all corners of Indonesia through the PKK (Family Welfare Education) program, which is a very strategic social capital. It is necessary to increase the participation of women in disaster management, so that the coverage of protection for families will be more optimal.